Food choices determinants in à la carte restaurants - Rita de Cássia Ribeiro; Carolina Fagundes Silveira Teixeira; Rita de Cássia Marques; Edgar Gastón Jacobs Flores Filho (O Mundo da Saúde)
It is remarkable the increase in the number of restaurants, especially à la carte ones, and the analysis of the determinants of food choices in these environments may suggest changes in the food pattern. In this sense, the aim of the present study was to characterize users of à la carte restaurants and analyze the factors related to the decisions made regarding consumption of different culinary options offered in these establishments. Data were collected from an electronic site created with questions related to food choices of people that go habitually to à la carte restaurants and by visits to restaurants in this category to investigate the menus. In addition to the descriptive analyses, sex and schooling influence on the variables related to the food choices were verified. In order to analyze the correlation between age and monthly use of these establishments, a correlation coefficient was calculated. For the presentation and comparison of the most identified attributes in the menus a median and 95% confidence intervals were used. It was verified that sex, age and schooling affected in a significant way the decisions made by the users of these à la carte restaurants. Information such as price and ingredient descriptions was present in most establishments, but the users considered, in addition to their preferences, the sensory characteristics of the plates, an aspect poorly explored in the menus. Use of restaurants in this category may indicate the acquisition of a new habit and suggest changes in the users’ food patterns.